1995
DOI: 10.3109/02844319509034329
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological, Morphological, and Morphometric Effects of Aging on Nerve Regeneration in Rats

Abstract: To investigate the influence of age on the process of nerve regeneration, the right common peroneal nerves of 14 2 month old and 14 10 month old rats were transected and resutured. At four and eight weeks after the nerve repair, the motor nerve conduction velocity (MNCV), latency, and amplitude of the evoked potential from the peroneus longus muscle were measured. The number of regenerated myelinated fibres, axon diameter, axon area, axon circumference, and myelin thickness were also measured. Compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…The progressive decline of NCV with age has been already reported in the literature, but the association has been described either as linear or quadratic [4,24]. Our findings are in agreement with the notion that NCV declines linearly with age since we were unable to detect any departure from a linear decline across the entire life span.…”
Section: Discussionsupporting
confidence: 91%
“…The progressive decline of NCV with age has been already reported in the literature, but the association has been described either as linear or quadratic [4,24]. Our findings are in agreement with the notion that NCV declines linearly with age since we were unable to detect any departure from a linear decline across the entire life span.…”
Section: Discussionsupporting
confidence: 91%
“…Hofteig et al [17], studying agedependent loss of major peripheral nerve lipids after nerve transection in animals of differing ages, established that there was a significantly faster clearance of neural debris in younger animals. This finding is in agreement with the recent findings by Choi et al [18] who showed that the recovery rate is greater in 2-month-old than in 10-month-old rats, particularly at 4 weeks after nerve repair, and this delay was attributed mainly to slower wallerian degeneration in older animals. It is possible that faster clearance of debris may allow axon sprouts to grow within the Schwann tubes unimpeded towards the peripheral end organ.…”
supporting
confidence: 83%
“…In the LSE and LSR groups, fibers from groups III and IV also present an increase in conduction velocity, indicating that the maintenance of muscle activity act on the regenerating motoneurons. Choi et al (5) reported an increase in conduction velocity in the regenerating fibers. However, Horch and Lisney (23) reported a reduction in axon diameter (and conduction velocity) that should normalize with recovery with a long period after reinnervation.…”
Section: Nerve Recordingsmentioning
confidence: 95%